2019
DOI: 10.1016/j.nmd.2019.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Nusinersen initiated in infants during the presymptomatic stage of spinal muscular atrophy: Interim efficacy and safety results from the Phase 2 NURTURE study

Abstract: Spinal muscular atrophy (SMA) is a neurodegenerative disease associated with severe muscle atrophy and weakness in the limbs and trunk. We report interim efficacy and safety outcomes as of March 29, 2019 in 25 children with genetically diagnosed SMA who first received nusinersen in infancy while presymptomatic in the ongoing Phase 2, multisite, open-label, single-arm NURTURE trial. Fifteen children have two SMN2 copies and 10 have three SMN2 copies. At last visit, children were median (range) 34.8 [25.7-45.4] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
451
1
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 469 publications
(480 citation statements)
references
References 44 publications
15
451
1
13
Order By: Relevance
“…Based on the mechanism of SMN2splicing modifiers like nusinersen, it is likely that patients with a high number of SMN2 copies profit most from therapy. The NURTURE study demonstrated that children with 3 copies of SMN2 have a better outcome than those with 2 SMN2 copies [30]. This gives hope that treatment in patients with 4 and more SMN2 copies will produce enough SMNprotein to live a normal life.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the mechanism of SMN2splicing modifiers like nusinersen, it is likely that patients with a high number of SMN2 copies profit most from therapy. The NURTURE study demonstrated that children with 3 copies of SMN2 have a better outcome than those with 2 SMN2 copies [30]. This gives hope that treatment in patients with 4 and more SMN2 copies will produce enough SMNprotein to live a normal life.…”
Section: Discussionmentioning
confidence: 99%
“…With the availability of new treatments for SMA and the technical feasibility of a population based newborn screening program, presymptomatic treat-ment of children with SMA has become a realistic option. As with many genetic disorders, a growing amount of data suggests presymptomatic treatment leading to far better outcomes than post-symptomatic therapy [30] does. However, in contrast to nearly all children with 2 or 3 copies of the SMN2 gene who develop the severe or intermediate phenotypes of SMA type 1 or type 2, the situation in patients with 4 and more copies is less clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The currently approved treatments for SMA provide optimal benefit if administered presymptomatically . As treated infants with SMA grow and develop, new phenotypes in SMA are emerging.…”
Section: Introductionmentioning
confidence: 99%